Silicone-recycled pyrolyzed fillers for enhanced thermal - and flame - resistant silicone elastomers. (June 2022) - Hajj, Raymond; Brunel, Raphael; Sonnier, Rodolphe; Longuet, Claire; Ganachaud, François
Highlights: A new method to recycle silicone elastomer waste. SIOC ceramic as original filler in silicone materials. Enhanced isothermal properties. Improved fire resistance by shielding effect. Abstract: Two types of fillers were prepared by controlled pyrolysis of a commercial silicone elastomer. An aerobic process led to the formation of a silica powder while an anaerobic pyrolysis generated a silicon-carbon-oxide (SiOC) ceramic. Each filler was incorporated into a silicone gum and thus-prepared obtained formulations were further crosslinked with peroxide to prepare new silicone materials. Silica powder allowed controlling the mechanical properties of the materials whereas enhanced thermal stability was brought by the ceramic; mixing both fillers generated materials with joint properties (tensile strength of about 2 MPa, elongation at break of 300%, onset of degradation at 470 °C). The flame resistance behavior of these silicone materials was tested by cone calorimetry. Early formation of an insulating layer on the heat-exposed surface moderated the heat release (total heat release of 16.4 kJ/gPDMS ) and increased final residue (above 50%) compared to commercial silica-filled elastomers. This work opens new possibilities to transform silicone waste into useful inorganic fillers and produce new performant thermal-resistant silicone materials.